KiDS-450: cosmological constraints from weak-lensing peak statistics – II: Inference from shear peaks using N-body simulations. Issue 1 (26th October 2017) - Martinet, Nicolas; Schneider, Peter; Hildebrandt, Hendrik; Shan, HuanYuan; Asgari, Marika; Dietrich, Jörg P.; Harnois-Déraps, Joachim; Erben, Thomas; Grado, Aniello; Heymans, Catherine; Hoekstra, Henk; Klaes, Dominik; et al.
Abstract: We study the statistics of peaks in a weak-lensing reconstructed mass map of the first 450 deg 2 of the Kilo Degree Survey (KiDS-450). The map is computed with aperture masses directly applied to the shear field with an NFW-like compensated filter. We compare the peak statistics in the observations with that of simulations for various cosmologies to constrain the cosmological parameter S_8 = σ _8 Ω _m/0.3, which probes the (Ωm, σ8 ) plane perpendicularly to its main degeneracy. We estimate S 8 = 0.750 ± 0.059, using peaks in the signal-to-noise range 0 ≤ S/N ≤ 4, and accounting for various systematics, such as multiplicative shear bias, mean redshift bias, baryon feedback, intrinsic alignment, and shear–position coupling. These constraints are ∼ 25 per cent tighter than the constraints from the high significance peaks alone (3 ≤ S/N ≤ 4) which typically trace single-massive haloes. This demonstrates the gain of information from low-S/N peaks. However, we find that including S/N < 0 peaks does not add further information. Our results are in good agreement with the tomographic shear two-point correlation function measurement in KiDS-450. Combining shear peaks with non-tomographic measurements of the shear two-point correlation functions yields a ∼20 per cent improvement in the uncertainty on S 8 compared to the shear two-point correlation functions alone, highlighting the great potential of peaks as a cosmological probe.